Rapid shifts in picoeukaryote community structure in response to ocean acidification - Meakin, Nicholas G; Wyman, Michael (The ISME Journal, 2011)
Rapid shifts in picoeukaryote community structure were observed during a CO2 perturbation experiment in which we followed the development of phytoplankton blooms in nutrient-amended mesocosms under present day or predicted future atmospheric pCO2 (750 μatm, seawater pH 7.8). Analysis of rbcL clone libraries (encoding the large subunit of RubisCO) and specific QPCR assays showed that two prasinophytes closely related to Micromonas pusilla and Bathycoccus prasinos were present but responded very differently to high CO2/acidification. We found that the abundance of Micromonas-like phylotypes was significantly higher (>20-fold) under elevated CO2/low pH, whereas the Bathycoccus-like phylotypes were more evenly distributed between treatments and dominated the prasinophyte community under ambient conditions. Rapid shifts in picoeukaryote community structure were observed during a CO2 perturbation experiment in which we followed the development of phytoplankton blooms in nutrient-amended mesocosms under present day or predicted future atmospheric pCO2 (750 μatm, seawater pH 7.8). Analysis of rbcL clone libraries (encoding the large subunit of RubisCO) and specific QPCR assays showed that two prasinophytes closely related to Micromonas pusilla and Bathycoccus prasinos were present but responded very differently to high CO2/acidification. We found that the abundance of Micromonas-like phylotypes was significantly higher (>20-fold) under elevated CO2/low pH, whereas the Bathycoccus-like phylotypes were more evenly distributed between treatments and dominated the prasinophyte community under ambient conditions.